Rancang Bangun Alat Bantu Penggulung Benang Kain Tenun Gedogan Dengan Metode Overall Equipment Effectiveness - Anas, M. Rizal; Widhiada, I Wayan; Winaya, I Nyoman Suprapta (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstract This research design a screw rolling tool using two 12 Volt 200 rpm DC motors using the overall equipment effectiveness method to measure the effectiveness value of the machine which has three productivity elements measured, namely availability rate, performance rate, and quality rate using 3-speed variation namely 50 rpm, 100 rpm, and 200 rpm. The performance of the automatic winding tool is more effective than the manual yarn winding tool at a speed of 200 rpm which has met the global standard of OEE value with a value of 95% with the results of rolls that have flatness and do not experience tangles on the roll. Keywords: Thread Winding Aid, DC Motor, Overall Equipment Effectiveness, Availability Rate, Performance Rate, Quality Rate